2018
DOI: 10.1093/gerona/gly059
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Melatonin Against Age-Associated, Sarcopenia-Dependent Tubular Aggregate Formation, Lactate Depletion, and Mitochondrial Changes

Abstract: To gain insight into the mechanism of sarcopenia and the protective effect of melatonin, the gastrocnemius muscles of young (3-4 months), early-aged (12 months), and old-aged (24 months) wild-type C57BL/6J female mice were examined by magnetic resonance and microscopy. Locomotor activity, lactate production, and nuclear apoptosis were also assessed. The results support the early onset of sarcopenia at 12 months of age, with reduction of muscle fiber number, muscle weight/body weight ratio, lactate, and locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 70 publications
4
51
0
Order By: Relevance
“…Furthermore, inflammation and lower glycolytic potential, assessed as lactate amount, strongly influenced skeletal muscle metabolism in sarcopenia [89]. In the gastrocnemius muscle of aged mice altered autophagy, nuclear fragmentation and abnormal lactate production were detected, but all these adverse changes decreased by oral melatonin intake [90]. Remarkably, melatonin supplementation in NLRP3 KO mice was particularly beneficial to retard the onset of sarcopenia in gastrocnemius muscle in aged animals [91].…”
Section: Melatonin Alleviates Skeletal Muscle Disorders In Vitro and mentioning
confidence: 99%
“…Furthermore, inflammation and lower glycolytic potential, assessed as lactate amount, strongly influenced skeletal muscle metabolism in sarcopenia [89]. In the gastrocnemius muscle of aged mice altered autophagy, nuclear fragmentation and abnormal lactate production were detected, but all these adverse changes decreased by oral melatonin intake [90]. Remarkably, melatonin supplementation in NLRP3 KO mice was particularly beneficial to retard the onset of sarcopenia in gastrocnemius muscle in aged animals [91].…”
Section: Melatonin Alleviates Skeletal Muscle Disorders In Vitro and mentioning
confidence: 99%
“…Previous studies on testis reported the protective effects of melatonin on reduction of non-enzymatic lipid oxidation of rat testicular mitochondria and microsomes [ 43 ], reduction of irradiation-induced damage of rat testes [ 44 ], treatment of oxidative testicular damage induced by 2-bromopropane through its ROS scavenger and antiapoptotic effect [ 45 ], minimizing the testicular ischemic injury of rats’ cellular organelles by preserving the DNA against oxidative damage [ 46 ], reducing of germ cell apoptosis and cadmium-induced cellular stress in testes [ 47 ], alleviation of testicular damage and attenuation of germ cell apoptosis in hyperlipidemic mice [ 48 ], removing the cigar smoke-induced testicular injury and restoring normal testicular tissue [ 49 ]. Melatonin dose of 10 mg/kg used in this study has also revealed significant anti-aging beneficial effects in SAM and wild-type mice [ 24 , 26 , 50 ]. Furthermore, therapeutic doses of the melatonin ranging from 5 mg to 50 mg/kg bw were previously reported [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study findings proved the anti-oxidant potential of melatonin, which was reported previously in many researches. These studies reported that melatonin modulated apoptotic proteins, hence reducing apoptosis [ 4] , improved vascular endothelial function [ 5] , resulted in efficient elimination of ROS and nitric oxide [ 6] , and provided protection against age-related mitochondrial dysfunction [ 7] . All of these miraculous effects of melatonin were welldisplayed in the current study, in the form of reduced apoptotic activity, enhanced cellular proliferation, enhanced vascularization, reduced inflammatory cells in CT, enhanced new collagen production, and diminished collagen destruction or hyalinization.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup II.b: Animals in this subgroup received Melatonin via gastric gavage at a dose of 10mg/kg/day dissolved in 1 ml of distilled water, for eight consecutive weeks [ 7] .…”
Section: Group IImentioning
confidence: 99%
See 1 more Smart Citation